The metastasis-associated gene MTA3 is downregulated in advanced endometrioid adenocarcinomas - Brüning, Ansgar; Jückstock, Julia; Blankenstein, Thomas; Makovitzky, József; Kunze, Susanne; Mylonas, Ioannis (Histology and histopathology, 2010)
The metastasis-associated gene MTA3 has an important function in invasion and metastasis of human cancer cells. Therefore, the aim of this study was to investigate the expression of this protein in endometrial adenocarcinomas and to analyse potential correlations between this nuclear transcription factor and estrogen receptors in endometrial adenocarcinomas. Additionally, we evaluated whether MTA3 might be a prognostic parameter in endometrioid adenocarcinomas. Endometrioid adenocarcinomas were obtained from 200 patients and immunohistochemically analysed for MTA3 and estrogen receptor alpha and beta (ER-alpha and ERbeta) expression. Overall, endometrioid adenocarcinomas of histological differentiation grade 3 demonstrated a significantly lower expression of MTA3 compared to carcinomas of histological grade 1 and 2 (p<0.05). MTA3 expression is reduced in endometrioid adenocarcinomas of poor differentiation, though without any correlation to ER-alpha and ER-beta expression. Furthermore, the expression of MTA3 did not affect progression-free, cause-specific and overall survival. Overall, MTA3 did not constitute an independent prognostic factor in this study, suggesting that MTA3 is not a useful marker to assess and identify high-risk patients with endometrial adenocarcinomas. Still, the downregulation of MTA3 predispose this cell type to be of high metastatic potential after malignant transformation, playing an essential, but as yet unknown role in human endometrial carcinogenesis.
Gesehen am 08.03.2023